A polymorphism of the ability to smell urinary metabolites of asparagus. Issue 6256 (20th December 1980) - Lison, M; Blondheim, S H; Melmed, R N
Abstract : The urinary excretion of (an) odorous substance(s) after eating asparagus is not an inborn error of metabolism as has been supposed. The detection of the odour constitutes a specific smell hypersensitivity. Those who could smell the odour in their own urine could all smell it in the urine of anyone who had eaten asparagus, whether or not that person was able to smell it himself. Thresholds for detecting the odour appeared to be bimodal in distribution, with 10% of 307 subjects tested able to smell it at high dilutions, suggesting a genetically determined specific hypersensitivity.